Holes - Sachar, Louis, 1954- (New York : Dell Yearling, 2000)
As further evidence of his family's bad fortune which they attribute to a curse on a distant relative, Stanley Yelnats is sent to a hellish correctional camp in the Texas desert where he finds his first real friend, a treasure, and a new sense of himself.
"A Yearling book.".
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
Books for the Teen Age (NYPL), April 1999.
Elem. School Library Collection, June 2000.
Keywords: Friendship -- Juvenile fiction; Homeless persons -- Juvenile fiction; Juvenile delinquency -- Juvenile fiction; Treasure troves -- Juvenile fiction; Buried treasure -- Fiction; Friendship -- Fiction; Homeless persons -- Fiction; Juvenile delinquency -- Fiction; Mystery and detective stories; Buried treasure -- Fiction; Friendship -- Fiction; Homeless persons -- Fiction; Juvenile delinquency -- Fiction; Mystery fiction